Insecticide application rate in coffee crop: Qualitative and quantitative aspects and efficacy of leaf miner control - Melo, Thiago Lima; Raetano, Carlos Gilberto [UNESP]; Cardoso, Adriana Dias; Moreira, Aldenise Alves; Leite, Suzany Aguiar; Castellani, Maria Aparecida (Coffee Science, 2020)
Leaf miner is a key coffee crop pest in Central and South America countries, especially in Brazil, where the insect causes considerable production losses. In the management of this insect pest, insecticide applications at reduced rates are fundamental for improve the operational capacity of the sprayer and the rational use of water. Thus, the aim of this study was to select a application rate that ensures effectiveness of cyantraniliprole, cartape hydrochloride and beta-cypermethrin insecticides in the leaf miner control, good spraying quality with varying application rates and low impact on natural parasitism. The qualitative and quantitative aspects of spraying with the Brilliant Blue marker were evaluated at the following rates: 28.1, 60.5, 80.2 and 180.0 L ha-1 and the efficacy of cyantraniliprole, cartape hydrochloride and beta-cypermethrin insecticides, with doses of the commercial formulations. Pest infestation and parasitism were determined before and after applications. Application rate interferes with qualitative aspects and spray deposition levels. Considering the quality-quantitative aspects and Agronomic Efficacy, rates between 80.2 and 180.0 L ha-1 are the most suitable for the control of this insect. Cyantra-niliprole insecticide is effective in controlling L. coffeella up to 45 DAA at rate of 180.0 L ha-1. The impact of cyantraniliprole, cartape hydrochloride and beta-cypermethrin insecticides on L. coffeella natural parasitism varies with application rates and time after application.
Keywords: Beta-cypermethrin; Brilliant blue marker; Cartape hydrochloride; Cyantraniliprole; Leucoptera coffeella